2012
DOI: 10.1109/tcsi.2012.2188954
|View full text |Cite
|
Sign up to set email alerts
|

A Very Low-Complexity 0.3–4.4 GHz 0.004 mm$ ^{2}$ All-Digital Ultra-Wide-Band Pulsed Transmitter for Energy Detection Receivers

Abstract: This paper presents a very low-complexity all-digital IR-UWB transmitter that can generate pulses in the band 0-5 GHz, requiring a silicon area lower than a PAD for signal I/O. The transmitter, suited to non-standardized low data rate applications, is prototyped in a 130 nm RFCMOS technology and includes analog control signals for frequency and bandwidth tuning. Center frequency is linearly selected with voltage supply, 0.5 V for the range 0-960 MHz and 1.1 V supply for the higher 3.1-5 GHz range. The architec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…The last part of the circuit, connected to monostable multivibrator output, is composed by a set-reset flip-flop followed by three inverters. They trigger the low complexity UWB-TX [17] creating the 3.3 GHz pulses transmitted by a AH086 multilayer Taiyo Yuden antenna. The UWB pulses length and frequency can be adjusted operating on and : we chose an impulse duration of 5 ns.…”
Section: Acquisition Unit Architecturementioning
confidence: 99%
“…The last part of the circuit, connected to monostable multivibrator output, is composed by a set-reset flip-flop followed by three inverters. They trigger the low complexity UWB-TX [17] creating the 3.3 GHz pulses transmitted by a AH086 multilayer Taiyo Yuden antenna. The UWB pulses length and frequency can be adjusted operating on and : we chose an impulse duration of 5 ns.…”
Section: Acquisition Unit Architecturementioning
confidence: 99%
“…Moreover, recent advances have shown that alldigital IR-UWB transmitters are feasible, thus making their adoption very attractive, considering the area occupation, flexibility (also in terms of scalability with respect to the technology node), robustness. The enclosed IR-UWB is the one designed in [20], mainly due to its wide frequency range (0.3 − 4.4 GHz), low power consumption (32 pJ /pulse at 4 GHz), area occupation (0.004 mm 2 ) and its all-digital design suited for OOK/S-OOK modulation. Further, its ability to operate in Sub-GHz band, where best tissue penetration conditions are possible, is a key feature to deploy Wireless Body Area Networks (WBAN) [21].…”
Section: Design and Implementationmentioning
confidence: 99%
“…1.4nJ ( 32 pJ /pulse at 4GHz [20]), corresponding to a power consumption (at full event rate) of P T X 0.47mW . Summing all the contributions, at full event rate in the above configuration, the estimated overall power consumption is P total = 8 × P R2F + P digital + P T X 1mW .…”
mentioning
confidence: 99%
“…microcontrollers). Moreover, a quasi-digital signal is directly compatible with asynchronous IR-UWB transceivers for low-power wireless communication [19], [20]. Therefore, we can design a wireless M4N chip able to transmit the nanosensor data to a remote acquisition and elaboration unit.…”
Section: Fast Zno-nws Assembling Onto M4n Chipmentioning
confidence: 99%